Reforming Legal Policy on the Out-of-Court Resolution of Criminal Cases through a Justice-Based Approach - Seraphinus Mariano Agung Serman; Pujiyono (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study examines the reform of legal policies governing the out-of-court resolution of criminal cases in Indonesia from the perspectives of restorative justice and Islamic law. It assesses the extent to which existing policies embody substantive justice and proposes future directions for legal reform. Using normative legal research with statutory, conceptual, and selected comparative approaches, the study analyzes regulations governing the police, prosecution service, judiciary, and national criminal law codification, and evaluates their relationship with restorative justice, maqāṣid al-sharīʿah, and ṣulḥ. Comparative analysis is conducted through selected legal models in Japan, the Netherlands and France. The study finds that although restorative justice has been formally institutionalized, its implementation remains fragmented due to regulatory inconsistencies, limited interinstitutional coordination, and the persistence of a retributive legal culture. Consequently, restorative justice has not yet functioned effectively as an integrated mechanism for victim recovery, offender accountability, and social reconciliation. Comparative findings indicate that effective out-of-court criminal case resolution requires harmonized legal standards, coordinated institutional authority, and enforceable mechanisms for victim protection. The enactment of Indonesia’s new Criminal Code and Criminal Procedure Code provides an important foundation for strengthening restorative justice through clearer coordination, supervision, and accountability mechanisms. These developments are also consistent with the Islamic legal principles of ṣulḥ (reconciliation), proportionality, and maṣlaḥah (public welfare), thereby reinforcing the normative legitimacy of restorative justice reform within Indonesia’s criminal justice system.